CROSS-PROTECTION OF COTTON AGAINST VERTICILLIUM WILT BY VERTICILLIUM NIGRESCENS - VAGELAS, IOANNIS; LEONTOPOULOS, STEFANOS (Emirates Journal of Food and Agriculture, 2015)
Two species of plant pathogenic fungi causing Verticillium wilt of cotton, Verticillium dalhiae Kleb. and V. nigrescens Pethybr., proved aggressive and weakly pathogen of cotton, respectively, and were used in this study. Cotton cultivars cvs 4S and Stoneville 453, susceptible to Verticillium wilt disease, were treated with both organisms in order to determine possible cross protection effects of V. nigrescens against V. dahliae. Results showed that the cotton plants which were inoculated on the same day as V. dahliae prior to inoculation by V. nigrescens were showing aggressive wilt symptoms of Verticillium wilt of cotton. However, the plants inoculated on the same day as V. nigrescens prior to inoculation by V. dahliae resulted low to mild wilt symptoms. Control of Verticillium wilt of cotton was obtained when V. nigrescens was inoculated four days prior to inoculation by V. dalhiae. Those promising results where further explained by data obtained from the transpiration rates of the mass flow of sap in cotton stems and demonstrated that conidia of V. nigrescens could protect the cotton plants from virulent conidia of V. dahliae.